Seven ways to get a grip on using participant observation in medical education research (Canadian Medical Education Journal, 2025)
Medical education phenomena are complex, and researchers need to use diverse methods to explore topics. Participant observation is a qualitative research method that connects researchers to human interactions, allowing them to experience firsthand behaviours, conversations, characteristics, and qualities related to the phenomenon under study. It can provide unique insights, beyond those of participant narratives, and enhance understanding. However, this method is rarely used in medical education research; it is challenging and resource-intensive to implement, which likely discourages researchers from using it. To help researchers get a grip on using it in medical education research, we offer seven recommendations for planning participant observation: Determine the study setting(s), Identify key interest-holders and establish relationships, Determine the researcher-participant relationship to be established, Take steps to minimize reactivity to research, Use knowledge to guide data collection procedures, Use knowledge to inform instrument development, and Anticipate possible dilemmas and be mindful of unanticipated ones. We urge researchers to consider participant observation when appropriate to advance methods in medical education research.